2021
DOI: 10.1016/j.ijrobp.2021.05.114
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Toxicity and Quality-of-Life Profiles in Patients With Head and Neck Cancer Treated With Definitive Radiation Therapy or Chemoradiation

Abstract: Purpose: Radiation therapy is an effective but burdensome treatment for head and neck cancer (HNC). We aimed to characterize the severity and time pattern of patient-reported symptoms and quality of life in a large cohort of patients with HNC treated with definitive radiation therapy, with or without systemic treatment. Methods and Materials: A total of 859 patients with HNC treated between 2007 and 2017 prospectively completed the European Organization for Research and Treatment of Cancer (EORTC) Quality of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…For global scores, this was determined as a difference of 9.43 points, for the functional domains scores ranged between 9.6 and 12.8 points and for fatigue and constipation the clinically relevant difference was found to be 11.62 and 11.09, respectively. The improving trend in symptom scores found in this study was comparable to another study describing the trend of HRQOL symptom scores in patients with HNSCC (Van den Bosch et al, 2021) and might be the driver of the higher summary score in patients with delayed treatment initiation. Albeit, the difference in HRQOL trends seems not clinically relevant.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For global scores, this was determined as a difference of 9.43 points, for the functional domains scores ranged between 9.6 and 12.8 points and for fatigue and constipation the clinically relevant difference was found to be 11.62 and 11.09, respectively. The improving trend in symptom scores found in this study was comparable to another study describing the trend of HRQOL symptom scores in patients with HNSCC (Van den Bosch et al, 2021) and might be the driver of the higher summary score in patients with delayed treatment initiation. Albeit, the difference in HRQOL trends seems not clinically relevant.…”
Section: Discussionsupporting
confidence: 89%
“…The results in this study focused solely on the EORTC QLQ‐C30 and not on other PROMs. Future studies can additionally consider studying trends in other PROMs, such as the EORTC QLQ‐HN35; however, a recent study by Van den Bosch reported similar trends for C30 and HN35 (Van den Bosch et al, 2021). Furthermore, HPV status was not known in all oropharyngeal patients, who were mainly represented in the group with delayed treatment initiation.…”
Section: Discussionmentioning
confidence: 98%
“…18 Collectively, these findings suggest a critical need to support HNC caregivers during patient radiotherapy, a time of substantial patient care needs. 19-21…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the burden of acute and late side effects is still substantial despite the introduction of modern radiation techniques. [4][5][6][7] Currently, 650 new patients with OPSCC are diagnosed annually in the Netherlands of which 40%-50% are HPV-negative. If we could predict treatment response in this patient group before or early during treatment, this would open the door to clinical trials in which a more personalised treatment could be investigated, for example, intensified (or in contrast, for those with poorer performance status, palliative therapy) for poor responders, and possibly less intense and thereby a less toxic therapy for good responders.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%